The impact of work gamification on Chinese employee creativity: a moderated mediation model - Liu, Hui; Gao, Jiachen (Frontiers in Psychology, 2025)
IntroductionAs economic and social development continues, the values and behavioral patterns within society are undergoing profound transformations, posing significant challenges to traditional enterprise management models. To enhance employee engagement and improve workplace efficiency, gamification design has increasingly gained attention in both theoretical discourse and practical enterprise management. This study aims to elucidate the mechanisms by which workplace gamification influences employee creativity, addressing urgent managerial challenges arising from the normalization of remote work and the increasing prevalence of Generation Z employees.MethodsBased on flow theory, this study analyzed survey data collected from 217 Chinese enterprise employees (84 males, 133 females; 83.87% aged 18–42) from January to February 2024. Intrinsic motivation was employed as the mediating variable, and employee acceptance of work gamification served as the moderating variable.ResultsThe findings reveal that work gamification significantly enhances employee creativity, with intrinsic motivation serving a pivotal mediating role. Furthermore, employee acceptance of work gamification moderates the relationship between gamification and intrinsic motivation; specifically, a higher level of acceptance strengthens the positive impact of gamification on intrinsic motivation. Additionally, acceptance level further moderates the mediating effect of intrinsic motivation on the relationship between work gamification and creativity. When employee acceptance is high, the indirect effect of gamification on creativity through intrinsic motivation is more pronounced.DiscussionThe study offers substantial theoretical and practical contributions. Its findings enrich theoretical understanding regarding workplace gamification mechanisms (e.g., points, task challenges, virtual rewards) and boundary conditions, while also providing practical insights for enterprises aiming to effectively utilize gamification strategies to stimulate employee creativity.